Analisis Pengendalian Internal dan Faktor-Faktor yang Mempengaruhi Kecurangan Akuntansi pada Perusahaan di Kota Batam - Dinda Sukmarianti; Dian Efriyenti (Ekonomis: Journal of Economics and Business, 2023)
In the current era, cases of accounting fraud in companies in Batam City occur repeatedly. Many mass media are reporting on this so that for the public, the case of accounting fraud tendency does not seem to be an open secret anymore. The purpose of this study is to analyze the influence of internal control on accounting fraud factors in companies in Batam City. The analytical methods used in this study are quantitative analysis and use descriptive statistical tests, validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. Taking samples using the purposive sampling method, researchers collected primary data using questionnaires given to accounting staff at companies in Batam City with a total sample of 122 respondents. The results showed that the effectiveness of internal control affects the tendency of accounting fraud with a sig value of 0.007>0.05; Observance of Accounting Rules and Unethical Behavior affects the Tendency of Accounting Fraud with a sig value of 0.001<0.05; The suitability of compensation simultaneously affects the Tendency of Accounting Fraud with a sig value of 0.010<0.05. The value of the coefficient of determination (R Square) is 0.720 or 72%, while the remaining 28% is explained by variations in other variables that are not present in this study model.